Controlling directions of electron flow by light: A case study on TiO2 film with azo dyes. (February 2019) - Zhang, Lei; Li, Cunyu; Li, Jingfa; Jiang, Fan
Abstract: Photo-responsive molecules have been widely investigated since they exhibit potential applications in optoelectronics and molecular devices. Although the photocurrents in some photo-responsive systems can be successfully turned 'on' and 'off' via light irradiation, the modulation of the vastly different directions of electron flow have seldom been realized by light (i.e., induce electron flow in opposite directions simply by light). In this manuscript, we provide evidence that the electron flow directions could be successfully controlled by light, using a molecule/TiO2 hybrid system based on azo dyes (methyl red and ethyl red) as an example. In particular, a light-induced current exists when a UV light is employed, while the photocurrent direction isreversed when a visible light is employed. Possible origins of such peculiar photoelectrochemical behaviors are suggested, based on the optimized structures and electronic/optical properties determined from the first principles calculations. We expect that with further molecular engineering and structure optimization, the electron flow directions as well as the photocurrent intensities in functional materials could be better controlled by light, which provide a foundation for the fundamental understanding of the photo-responsive behaviors in advanced functional materials, and may pave the way for the design of novel optoelectronic devices and solar fuel systems in which the opposite electron transfer directions could be manipulated remotely by light sources. Graphical abstract: Highlights: The directions of the current can be controlled by light. Two competing charge transfer routes might exist. Their photocurrents and optical properties are characterized.